Active Tuberculosis Case Discovery Using the Adaptation Model in the City of Yogyakarta - Dewi, Setyogati Candra; Sunarti; Suryani, Dyah; Rokhmayanti (Jurnal Kesehatan, 2024)
Pendahuluan: Indonesia menjadi salah satu negara dengan beban TBC tertinggi kedua di dunia. Menuju elminasi TBC 2030, pemerintah menyusun kerangka akselerasi program TBC diantaranya berupa active case finding (ACF), sebagai upaya aktif mencari orang berisiko dan bergejala TBC dengan kegiatan pelacakan kontak dan skrining. Skrining menggunakan Chest x-ray (CXR) dinilai lebih sensitif daripada dengan pendekatan gejala, mengingat sebagian besar pasien TBC tidak memiliki gejala khas TBC. Pada tahun 2023 kegiatan ACF di Kota Yogyakarta dikembangkan dengan model adaptasi. Metode: Penelitian ini menggunakan metode deskriptif kuantitatif, menggambarkan hasil kegiatan ACF terdiri dari karakteristik peserta, jenis kelompok sasaran, skrining CXR, pemeriksaan TCM serta kontribusi ACF dalam program penanggulangan TBC. Hasil: Pada ACF dengan model adaptasi, peran Puskesmas dan lintas sektor lebih diutamakan. Kegiatan ACF di lakukan 88 kali dengan total peserta 7.423 orang, terduga TBC yang terjaring 1.403 orang (18.90%) dan 83 kasus TBC baru ditemukan. Peserta terbanyak adalah perempuan (54.41%), berusia 55 - ≤ 65 tahun (23.19%), dan berasal dari masyarakat sekitar lokasi ACF diselenggarakan (56.31%). Prosentase penemuan terduga dan kasus TBC terbanyak dari Puskesmas Pakualaman. Simpulan: ACF dengan model adaptasi di Kota Yogyakarta berkontribusi menemukan 22.92% terduga TBC dan 5.28% kasus TBC dari target yang harus ditemukan. Perlu dilakukan upaya kolaboratif antar sektor untuk memobilisasi kelompok sasaran yang tepat ke lokasi ACF seperti ODHIV, kontak serumah, pasien DM, balita dengan masalah gizi, kelompok laki-laki perokok dan pengguna alkohol.   Introduction: Indonesia is one of the countries with the second highest TB burden globally. Towards TB elimination by 2030, the government prepared a framework for accelerating the TB program, including active case finding (ACF), as an active effort to find people at risk and with symptoms of TB through contact tracing and screening activities. Screening using chest X-rays (CXR) is considered more sensitive than the symptom approach, considering that most TB patients do not have typical TB symptoms. In 2023, ACF activities in the City of Yogyakarta will be developed using an adaptation model. Method: Quantitative descriptive research describing the results of ACF activities consists of the characteristics of ACF participants, types of target groups, CXR screening, TCM examination, and ACF's contribution to the TB control program. Results: With the adaptation model, the role of Puskesmas and cross-sectors was prioritized in ACF. ACF was carried out 88 times with 7,423 participants; 1,403 people were suspected of having TB (18.90%), and 83 new TB cases were found. Most participants were women (54.41%), age group 55 - ≤65 years (23.19%), and came from the general public (56.31%). The highest percentage of suspected discoveries and TB cases came from the Pakualaman Health Center. Conclusion: With the adaptation model in Yogyakarta City, ACF contributed to finding 22.92% of suspected TB and 5.28% of TB cases of the target that had to be found. Collaborative efforts between sectors need to be made to mobilize the right target groups for ACF locations, such as PLHIV, household contacts, DM patients, toddlers with nutritional problems, groups of male smokers, and alcohol users.